2020
DOI: 10.5194/bg-17-6097-2020
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of trace metals from acid sulfate soils in sediments of the Kvarken Archipelago, eastern Gulf of Bothnia, Baltic Sea

Abstract: Abstract. Rivers draining the acid sulfate soils of western Finland are known to deliver large amounts of trace metals with detrimental environmental consequences to the recipient estuaries in the eastern Gulf of Bothnia, northern Baltic Sea. However, the distribution of these metals in the coastal sea area and the relevant metal transport mechanisms have been less studied. This study investigates the spatial and temporal distribution of metals in sediments at nine sites in the Kvarken Archipelago, which is th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Co transfer to particulate form was twice of that of Mn, which highlights Co complexation with flocs in addition to Mn oxyhydroxides. This interpretation is supported by the seaward enrichment patterns of Co and Mn in the front of Laihianjoki and Sulvanjoki, where both Co and Mn are strongly enriched up to 12 km distance, while a lower Co enrichment continues to at least 26 km distance (Virtasalo et al, 2020).…”
Section: Implications For Seaward Metal Transportmentioning
confidence: 78%
See 3 more Smart Citations
“…Co transfer to particulate form was twice of that of Mn, which highlights Co complexation with flocs in addition to Mn oxyhydroxides. This interpretation is supported by the seaward enrichment patterns of Co and Mn in the front of Laihianjoki and Sulvanjoki, where both Co and Mn are strongly enriched up to 12 km distance, while a lower Co enrichment continues to at least 26 km distance (Virtasalo et al, 2020).…”
Section: Implications For Seaward Metal Transportmentioning
confidence: 78%
“…A previous geochemical study of seafloor sediments in the front of Laihianjoki and Sulvanjoki found that AS soil-derived metals such as Cu and Co are strongly positively correlated with organic matter, particularly in the 2-6 µm sediment grain size range (Virtasalo et al, 2020). Also Al showed a weak correlation with this grain size range.…”
Section: Implications For Seaward Metal Transportmentioning
confidence: 86%
See 2 more Smart Citations
“…Specifically, it was concluded that Al, Fe, and Cu are deposited with organic matter close to the Vöyrinjoki river mouth, whereas Cd, Co, Ni, and Zn are preferentially transported farther out at sea, where they co-precipitate and are deposited with Mn oxyhydroxides (Nordmyr et al, 2008a, b;Nystrand et al, 2016). However, a recent study of seafloor sediments shows that Cu, Cd, Co, Ni, and Zn are all enriched at least 26 km away from the mouths of the nearby Laihianjoki and Sulvanjoki rivers, whereas the Mn enrichment extends less than 14 km from the river mouths (Virtasalo et al, 2020). This discrepancy between the observed seafloor metal distribution and the previously concluded seaward transport behaviour of the metals calls for further investigation of the flocculation process in boreal humus-rich rivers that are strongly impacted by acidity and metal release from AS soils.…”
Section: Introductionmentioning
confidence: 99%